Combining Experiments and Atom Probe Tomography-Informed Simulations on γ′ Precipitation Strengthening in the Polycrystalline Ni-Base Superalloy A718Plus - Kirchmayer, Andreas; Lyu, Hao; Pröbstle, Martin; Houlle, Frederic; Förner, Andreas; Huenert, Daniela; Göken, Mathias; Felfer, Peter; Bitzek, Erik; Neumeier, Steffen (Advanced Engineering Materials, 2020)
The strength of superalloys is strongly influenced by γ′ precipitates, whose size and volume fraction which can be adjusted by heat treatments. According to classical precipitation strengthening models, an increasing precipitate diameter should lead to a transition from weak to strong coupling of the dislocation pairs that form superdislocations in the γ′ phase. We show that long-term annealing of the Ni-base superalloy A718Plus at 670 and 680 °C increases the alloy's strength without significantly changing the grain size and η fraction. To understand the effect of the slight increase in γ′ size, detailed atom probe tomography (APT) was performed. Here, different field evaporation rates of the phases strongly affect the determination of the volume fraction when using the usual isosurface construction. This can be mitigated by considering the number density of atoms inside and outside the γ′ precipitates. Using an approximation of the precipitate shapes and arrangements from the APT data in atomistic simulations revealed that precipitate shearing by both, weakly and strongly coupled dislocations can occur in the same sample due to the wide distribution of precipitate sizes. These results highlight the need for advanced strengthening models that take into account the γ′ size distribution.
CRIS-Team Scopus Importer:2020-06-02
Keywords: atom probe tomography; atomistic simulations; Ni-base superalloys; precipitation strengthening; weak–strong pair coupling

Microstructural dependence of the fracture toughness of metallic thin films: A bulge test and atomistic simulation study on single-crystalline and polycrystalline silver films - Preiß, Eva; Lyu, Hao; Liebig, Jan Philipp; Richter, Gunther; Gannott, Florentina; Gruber, Patric A.; Göken, Mathias; Bitzek, Erik; Merle, Benoit (Journal of Materials Research, 2019)
The microstructure contribution to the very low fracture toughness of freestanding metallic thin films was investigated by bulge fracture tests on 200-nm-thick 100 single-crystalline and polycrystalline silver films. The single-crystalline films exhibited a significantly lower fracture toughness value (KIC = 0.88 MPa m1/2) than their polycrystalline counterparts (KIC = 1.45 MPa m1/2), which was rationalized by the observation of an unusual crack initiation behavior - characterized by twinning in front of the notch tip - during in situ testing in the atomic force microscope. Twinning was also observed as a dominant deformation mechanism in atomistic simulations. This twinning tendency is explained by comparing the resolved shear stresses acting on the leading partial dislocation and the full dislocation, which allows to develop a size- and orientation-dependent twinning criterion. The fracture toughness of polycrystalline samples was found to be higher because of the energy dissipation associated with full dislocation plasticity and because of crack meandering along grain boundaries.
CRIS-Team Scopus Importer:2019-09-27
Keywords: atomistic simulations; bulge testing; fracture testing; grain boundaries; silver; thin films; twinning criterion